The Influence of Information Technology Affordance on Purchase Intention: Case of TikTok Livestreaming Shopping - Chana Titania Azhari; Yulia Nur Hasanah (STIE Amkop Makassar, 2023)
As the majority of Generation Z consumers shift toward making purchases on social media sites, many platforms have incorporated live shopping into their marketing strategies Furthermore, live streaming shopping on TikTok is still a new phenomenon in Indonesia, and there is little study to explain why. This study aims to determine the influence of Information Technology Affordance (Visibility, Metavoicing, Guidance Shopping) on customers purchase intention on TikTok live streaming shopping from the standpoint of the IT Affordances theory. Data collection of this study was through the dissemination of questionnaires and using quantitative data analysis. Sampling is carried out by the non-probability sampling method with the purposive sampling method. The sample used in this study was 313 respondents. The analysis method used in this study was a multiple regression analysis test and was processed using SPSS 26 software. Based on the results of research from descriptive analysis, it shows that Visibility affordance, Metavoicing affordance, and Guidance Shopping affordance are in the “Very good” category. The results of multiple linear regression analysis can be concluded that simultaneously Information Technology Affordance (Visibility, Metavoicing, Guidance Shopping) have a significant effect on the customer purchase intention specifically on TikTok live streaming shopping. Based on the coefficient of determination test, it shows the influence of Information Technology Affordance (Visibility, Metavoicing, Guidance Shopping) on customer Purchase Intention on TikTok live streaming shopping is 81.9%.